Research trends in microRNA profiling as a biomarker for lung adenocarcinoma via liquid biopsy: A bibliometric analysis - Kartika, Aprilia I.; Dafip, Muchamad; Wijayanti, Nastiti; Heriyanto, Didik S.; Haryana, Sofia M.; Taroeno-Hariadi, Kartika W. (Narra J, 2025)
Research related to the development of diagnostic biomarkers in lung adenocarcinoma in various countries is important. Research on microRNA as a biomarker in lung adenocarcinoma varies depending on the population, specimen, and technology used for profiling and validation. The aim of this study was to map and analyze bibliometric data of publications related to the topic of microRNA as a candidate biomarker in lung adenocarcinoma and to determine any potential research gaps. A total of 8,506 articles were collected from Crossref, Google Scholar, Semantic Scholar, PubMed, and Scopus databases using Harzing's Publish or Perish platform. A systematic search was conducted using four keywords: “profiling,” “validating,” “microRNA,” and “lung adenocarcinoma,” and synonyms of these keywords based on the MeSH on NCBI. The data extraction process followed the chart from PRISMA-P. The article’s elimination was conducted using Mendeley Desktop and then was analyzed based on the authors' keywords using VOSviewer and Biblioshiny. A bibliometric analysis of 692 relevant articles identified four primary research clusters: (1) microRNA (19 keywords), which highlights its potential as a biomarker for early detection and diagnosis; (2) lung adenocarcinoma (18 keywords), reflecting advancements in lung cancer research; (3) liquid biopsy (19 keywords), emphasizing the growing interest in non-invasive diagnostic methods; and (4) bioinformatics (nine keywords), underscoring the role of computational approaches in transcriptomic analysis. As a primary topic, microRNAs have become a focal point of research for diagnosing lung cancer across various stages and as biomarkers for cancer cell proliferation, invasion, migration, and metastasis. Numerous studies have demonstrated the successful application of microRNAs in lung cancer diagnosis in the last decade, although the reported types of microRNAs are inconsistent. Therefore, further research on this topic should be continuously conducted, particularly to validate the types of microRNAs and the types of environments that influence them.